Lipidomic alteration of plasma in cured COVID-19 patients using ultra high-performance liquid chromatography with high-resolution mass spectrometry. Issue 3 (26th March 2021) - Bai, Yunpeng; Huang, Wendong; Li, Yaocai; Lai, Changchun; Huang, Sumei; Wang, Guangwen; He, Yuemei; Hu, Linhui; Chen, Chunbo
Abstract: Background: The pandemic of novel coronavirus disease 2019 (COVID-19) has become a serious public health crisis worldwide. The symptoms of COVID-19 vary from mild to severe among different age groups, but the physiological changes related to COVID-19 are barely understood. Methods: In the present study, a high-resolution mass spectrometry (HRMS)-based lipidomic strategy was used to characterize the endogenous plasma lipids for cured COVID-19 patients with different ages and symptoms. These patients were further divided into two groups: those with severe symptoms or who were elderly and relatively young patients with mild symptoms. In addition, automated lipidomic identification and alignment was conducted by LipidSearch software. Multivariate and univariate analyses were used for differential comparison. Results: Nearly 500 lipid compounds were identified in each cured COVID-19 group through LipidSearch software. At the level of lipid subclasses, patients with severe symptoms or elderly patients displayed dramatic changes in plasma lipidomic alterations, such as increased triglycerides and decreased cholesteryl esters (ChE). Some of these differential lipids might also have essential biological functions. Furthermore, the differential analysis of plasma lipids among groups was performed to provide potential prognostic indicators, and the change in signaling pathways. Conclusions: Dyslipidemia was observed in cured COVID-19 patients due to the viral infection and medical treatment, and the discharged patients should continue to undergo consolidation therapy. This work provides valuable knowledge about plasma lipid markers and potential therapeutic targets of COVID-19 and essential resources for further research on the pathogenesis of COVID-19.